2022
DOI: 10.1002/msc.1723
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth education and training in entry‐to‐practice physiotherapy programs in Australian universities: A qualitative study with university educators

Abstract: Background To explore attitudes to telehealth education and experiences incorporating telehealth education into entry‐to‐practice physiotherapy programs in Australia, from the perspective of university educators. Methods Qualitative design based on a constructivist paradigm and a phenomenological approach. Sixteen university educators (who had a responsibility for telehealth curriculum or oversight of the broader curriculum in an entry‐to‐practice physiotherapy programme at an Australian university) were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…27 Our findings support this notion showing that most students did not receive telehealth education and training during their program, nor did they have opportunities during clinical placements where telehealth was practically applied. Prior training and experiential learning have been shown to enhance students' understanding…”
supporting
confidence: 76%
See 3 more Smart Citations
“…27 Our findings support this notion showing that most students did not receive telehealth education and training during their program, nor did they have opportunities during clinical placements where telehealth was practically applied. Prior training and experiential learning have been shown to enhance students' understanding…”
supporting
confidence: 76%
“…A recent study exploring the implementation of telehealth education and training in entry‐to‐practice physiotherapy programs across Australia found that substantial variations exist in the content and volume of telehealth education and training delivered 27 . For example, some universities scaffold content across the entire program, some include learning outcomes, while others include only an ad‐hoc discussion during a tutorial 27 . Our findings support this notion showing that most students did not receive telehealth education and training during their program, nor did they have opportunities during clinical placements where telehealth was practically applied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While many formal mandated restrictions may have been eased by mid‐2022, there was still a common feeling of cautiousness among the general public and overall willingness to use telehealth as a viable option compared to in‐person care by both physiotherapists and patients. Aligning with these thoughts, qualitative interviews conducted with Australian physiotherapy university educators in 2022 found that they believed telehealth was here to stay as a part of contemporary physiotherapy practice (Davies et al., 2023).…”
Section: Discussionmentioning
confidence: 99%